Novel LoadProGen procedure for micro-grid design in emerging country scenarios: application to energy storage sizing. (October 2017) - Mandelli, S.; Brivio, C.; Moncecchi, M.; Riva, F.; Bonamini, G.; Merlo, M.
Abstract: This paper is devoted to describe the development, implementation and application of a novel procedure to properly design the electrification process in rural areas of Emerging Countries (EC). The procedure exploits a bottom-up approach, i.e. target applications are related to micro-grids devoted to satisfy the electrical needs of small communities. The procedure starts from microscopic data (i.e. single electric appliances) to effectively catch the customer needs (i.e. bottom ) and it matches them with the available energy sources in the target area. In particular, a tool named LoadProGen developed by the Energy4Growing research group of Politecnico di Milano, is presented: the mathematical approach proposed is detailed and a real field case study relevant to a micro-grid deployed in Tanzania is provided. The tool is based on the gathering of information about the target area, i.e. to get information from interview and field audit, and on a stochastic approach to build up realistic estimation of the electric load profile of the considered uses. The energy needs forecast (cfr. load profile) is then adopted in a second procedure devoted to design a micro-grid capable to properly feed the loads. In this work, for sake of exemplification, this latter is supposed to be a photovoltaic based micro-grid integrated with an electrochemical storage.